2014
DOI: 10.1590/s1413-41522014019000000652
|View full text |Cite
|
Sign up to set email alerts
|

Pós-tratamento de lixiviado de aterro sanitário com carvão ativado

Abstract: A degradação física, química e biológica da matéria orgânica presente dos resíduos sólidos gera um subproduto altamente poluidor, denominado lixiviado.Várias técnicas de tratamento aplicadas a esse efluente vêm sendo investigadas a fim de adequá-lo ao lançamento no corpo receptor sem causar prejuízos ao meio ambiente. Este trabalho teve como objetivo avaliar a aplicabilidade do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
1
5
0
8
Order By: Relevance
“…On the other hand, the treatment C1 showed a efficiency for removal of 66.56% of the true color, 67.65% of the COD and 67.99% of the apparent color. These values are compatible with other study developed by Kawahigashi et al (2014), in which authors verified the effectiveness of adsorption with commercial granular carbon of coconut endocarp as post treatment of landfill leachate, removing around 45 to 76% of COD, 95 to 100% of apparent color and 94 to 100 of the true color under conditions of pH = 4.0, Fe 3+ dose (mg Fe 3+ .L -1 ), initial COD of 303 mg.L -1 and height of bed of 9 cm. Vieira (2014), in a similar study, found that with the increase of the height of the bed from 10 cm to 30 cm, an improvement in performance was shown, increasing the rupture time and the percentage of removal at this condition.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the treatment C1 showed a efficiency for removal of 66.56% of the true color, 67.65% of the COD and 67.99% of the apparent color. These values are compatible with other study developed by Kawahigashi et al (2014), in which authors verified the effectiveness of adsorption with commercial granular carbon of coconut endocarp as post treatment of landfill leachate, removing around 45 to 76% of COD, 95 to 100% of apparent color and 94 to 100 of the true color under conditions of pH = 4.0, Fe 3+ dose (mg Fe 3+ .L -1 ), initial COD of 303 mg.L -1 and height of bed of 9 cm. Vieira (2014), in a similar study, found that with the increase of the height of the bed from 10 cm to 30 cm, an improvement in performance was shown, increasing the rupture time and the percentage of removal at this condition.…”
Section: Resultssupporting
confidence: 91%
“…Methylene blue index is a technique used to indirectly measure the pore size of the adsorbents; the materials with high methylene blue index indicate that the material analyzed is mesoporous (2 to 50 nm) (Kawahigashi et al, 2014). In this perspective, the activated carbon of RHA presents elusive indication of material with mesopores, according to the value of index of methylene blue found of 10.05 mg.g -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ello pudo deberse a la baja presencia de material en suspensión y predominio de sólidos disueltos en el lixiviado, asociados a la materia orgánica refractaria, la cual junto con el color verdadero han sido efectivamente removidos en postratamiento de lixiviados por adsorción, como lo han reportado Kawahigashi et al (2014).…”
Section: Resultsunclassified
“…En ella se puede apreciar que la columna de adsorción asumió de manera mayoritaria la remoción de la DQO, cuyas eficiencias medias calculadas con relación al efluente del filtro de antracita en las fases 1, 2 y 3 fueron respectivamente de 60,2, 43,7 y 23,6%. Tales eficiencias son comparables a las reportadas por Kawahigashi et al (2014), quienes evaluaron el postratamiento de los lixiviados de la ciudad de Rolândia, en el estado de Paraná-Brasil, inicialmente sometidos a stripping de amoníaco, seguido de tratamiento biológico por lodos activados y posteriormente por coagulación, floculación y sedimentación, así como por adsorción mediante carbón activado granular. En dicha experiencia, los autores registraron eficiencias de remoción entre 45 y 76% de la DQO por medio de la adsorción con diferentes tipos de carbón activado, para un tiempo de contacto de 20 minutos.…”
Section: Resultsunclassified
See 1 more Smart Citation